The Impact of Job Burnout towards Job Performance among Nurses - Dayang Nailul Munna, Abang Abdullah; Fong, Chui Yuen (IEEE, 2011)
The aim of this study was to determine the relationship between job burnout and job performance among nurses. The factors of interest in this study were components of job burnout, which included emotional exhaustion, depersonalization, and diminished personal accomplishment; and job performance of nurses. Survey questionnaire was used to collect the data needed for analysis, which was adapted and modified from Maslach Burnout Inventory (MBI). The respondents were nurses from the private hospital at Perak. Data collected was analyzed using SPSS version 12.0 for Window, and the methods of analysis were Pearson correlation and multiple regression analysis. The findings of this study revealed that there were significant correlations between emotional exhaustion (r=0.305, p=0.006), depersonalization (r=0.239, p=0.031) and job performance. Meanwhile, this study failed to establish a relationship between diminished personal accomplishment and job performance. On the other hand, multiple regression analysis showed that emotional exhaustion was the dominant factor that affecting job performance (β=0.305, r2=0.093). In conclusion, nursing profession is at high risk of job burnout or particularly emotional exhaustion, which will jeopardize nurses' job performance and eventually contribute to deterioration in quality of care.